Bildfolgenbasierte Gewinnung und Nutzung partikelindividueller Bewegungsinformation in der optischen Schüttgutsortierung - Maier, Georg (Karlsruher Schriftenreihe Fahrzeugsystemtechnik, 2022)
Sensor-based sorting enables the separation of individual particles from a material stream. In this work, a novel sorting system using an area-scan camera is investigated. The use of high-speed cameras raises exciting research questions from a computer science perspective regarding the extraction and use of more advanced features, especially motion information about the materials to be sorted.